Structural, elastic, and optical properties of holmiumytterbium-doped borotellurite glass for possible applications in optical fiber sensing - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2024)
Structural, elastic, and optical properties of holmiumytterbium-doped borotellurite glass for possible applications in optical fiber sensing by Muhammad Noorazlan Abd Azis